Water-volume variations of Lake Hulun estimated from serial Jason altimeters and Landsat TM/ETM+ images from 2002 to 2017. Issue 2 (17th January 2019) - Yuan, Cui; Gong, Peng; Liu, Caixia; Ke, Changqing
ABSTRACT: Lake Hulun is the fifth largest lake in China. The dramatic water-volume variations since the 21th century has aroused concerns from local and transboundary water resource authorities. To track its dynamics during the past sixteen years with no aid of in-situ data, serial Jason altimeters and optical remote sensing images were integrated to reconstruct the time series of the water-volume variations. We developed a workflow consisting of four procedures: 1) Deriving the water-level time series using Jason-1, Jason-2 and Jason-3 after applying a feature-based waveform classification method and a targeted waveform retracking strategy; 2) Extracting the water-area by using Landsat images; 3) Establishing the relationship between water-level and water-area; and 4) Reconstructing the water-volume variation time series by integrating the water-level time series and the relationship derived from 3). We found that Lake Hulun has gone through three stages of changes: 1) Period one (2002–2009), water-level and volume dropped significantly at a rate of −0.40 m yr −1 and −0.73 km 3 yr −1, respectively. 2) Period two (2010–2012), the water-level and volume were relatively stable. 3) Period three (2013–2015), the water-level and volume began to rise rapidly at the rates of 1.09 m yr −1 and 1.99 km 3 yr −1, respectively. In addition, two significant change years (2007 and 2013) were detected, which corresponded well with extreme climatic conditions. Preliminary analyses indicate that the water-volume variations are closely related to precipitation and temperature anomalies in wet seasons.